Acute immune stress improves cell resistance to chemical poison damage in SP600125-induced polyploidy of fish cells in vitro. Issue 84 (January 2019) - Mo, Yanxiu; Fan, Yunpeng; Fu, Wen; Xu, Wenting; Chen, Shujuan; Wen, Yuanhui; Liu, Shaojun; Peng, Liangyue; Xiao, Yamei
Abstract: Previous research has indicated that the small compound, SP600125, could induce polyploidy of fish cells, and has established a stable tetraploid cell line from diploid fish cells. In order to explore how fish cells maintain homeostasis under SP600125-stress in vitro, this study investigates impacts of SP600125-stress on intracellular pathways, as well as on regulation of the cellular homeostasis feedback in fish cells. Transcriptomes are obtained from the SP600125-treated cells. Compared with unigenes expressed in control group (crucial carp fin cells), a total of 2670 and 1846 unigenes are significantly upregulated and downregulated in these cells, respectively. Differentially expressed genes are found, which are involved in innate defense, inflammatory pathways and cell adhesion molecules-related pathways. The SP600125-stress enhances cell-mediated immunity, characterized by significantly increasing expression of multiple immune genes. These enhanced immune genes include the pro-inflammatory cytokines (IL-1β, TNF-ɑ, IL-6R), the adaptor signal transducers (STAT, IκBɑ), and the integrins (ɑ2β1, ɑMβ2). Furthermore, mitochondria are contributed to the cellular homeostasis regulation upon the SP600125-stress. The results show that acute inflammation is an adaptive and controlled response to the SP600125-stress, which is beneficial for alleviating toxicity by SP600125. They provide a potential way of breeding fish polyploidy induced by SP600125 in the future research. Highlights: Intracellular pathways and regulation of cellular homeostasis in SP600125-stress fish cells. Enhancement of SP600125-stress to cell-mediated immunity in fish cells. Adjustment of SP600125-stress to mitochondria functions in fish cells.